A Descriptive Study of the Characteristics of Older Adults with Hypertension - Farida Latif (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Hypertension is a common chronic disease among older adults and increases the risk of stroke, heart disease, kidney dysfunction, disability, and premature mortality. Identifying patient characteristics is necessary for developing appropriate hypertension-management programmes at the primary healthcare level. Research Objective: This study aimed to describe the characteristics of older adults with hypertension at the Poasia Primary Health Care Centre, Kendari. Methods: This quantitative study employed a descriptive design involving 42 older adults with hypertension selected through purposive sampling. Data were collected using structured questionnaires, medical records, anthropometric assessments, and direct blood pressure measurements. The data were analysed using univariate analysis and presented as frequencies and percentages. Results: Most respondents were aged 60–69 years (57.1%), female (61.9%), had primary-school education (42.9%), and were not working or were housewives (59.5%). Grade 1 hypertension was identified in 54.8% of respondents, while 59.5% reported a family history of hypertension and 57.1% had comorbidities. More than half were overweight or obese (54.8%). Although 64.3% regularly took antihypertensive medication and 59.5% routinely attended healthcare examinations, several respondents demonstrated irregular medication use and follow-up attendance. Conclusion: Older adults with hypertension had diverse demographic and clinical characteristics requiring comprehensive management. Regular monitoring, medication-adherence support, nutritional counselling, physical activity, and family involvement should be strengthened to improve hypertension control and prevent complications.